Belajar dari Kegalalan Politik Pengelolaan SDA Orde Baru: Studi Kasus Kalimantan Timur - Jemadu, Aleksis (Indonesian Journal of International Law, 2021)
The province of East Kalimantan has the largers tropical forests in Indonesia. throughout the era of the New Order government under President Soeharto the natural resources especially tropical forests were sistematically exploited without any serious effort on the part of the government and private companies to take care of the social and environmental aspect of such exploitation. As a result, severe environmental degradation took place and the local people in the country side lost their sources of livelihood. In the midst of the presence of multinational corporations and private forest concessionaires ironically there were enclaves of poverty. In this area of regional autonomy there is much doubt that the situation could get better as local government authorities tend to repeat past mistakes and they are unable to control the existance practice of illegal logging. This writing will propose some policy suggestions that might be helpful for promoting the principles of sustainable development and putting an end to the phenomenon of “the tragedy of the commons”.